Faktor Kejadian Anemia pada Pasien Kanker yang Mendapat Radioterapi dan atau Kemoterapi - Alpha Olivia Hidayati; Siti Arifah (Politeknik Kesehatan Tanjung Karang, 2020)
Base on research, radiotherapy can reduce cancer recurrence in 10 years from 35% to 19,3% in breast cancer. However, the therapy given affects the life quality of patients, one of which is anemia. Anemia causes a decrease in response and tolerance to treatment. This study aims to determine the factors associated with the incidence of anemia in cancer patients who receive radiotherapy and or chemotherapy. This study was an observational analytic study with a cross-sectional design. The method of sampling with consecutive sampling with a minimum sample size of 47. The result showed the age of a p-value (0,321)>0,05, the number of fractions a p-value (0,181)>0.05, the frequency of light that had been conducted a p-value (0,160)>0,05, type of radiotherapy a p-value (0,933)>0,05, setting radiotherapy a p-value (0,769)>0,05, history of blood transfusion during chemotherapy a p-value (0,411)>0,05 and nutrient intake (Protein a p-value (0,337)>0.05, iron a p-value (0,086)>0,05, zinc a p-value (0,411)>0,05, folic acid a p-value (0,963)>0,05, vitamin C a p-value (0,240)>0,05). Meanwhile, the total radiation dose received by respondents during one period of radiotherapy showed that there was a relationship with the incidence of anemia with a p-value (0,045)<0,05. As conclusions, that there was no significant relationship between age, type of cancer, number of fractions, frequency of light that had been conducted, type of radiotherapy, radiotherapy settings, history of blood transfusion during chemotherapy and nutrient intake, while the total radiation dose given to respondents showed a significant relationship with anemia incidence.